Individualised Care Scale-Nurse: Construct validity and internal consistency of the Spanish version - Rodríguez-Martín Beatriz; Gutiérrez Irene García-Camacha; Caro-Alonso Pedro Angel; Suhonen Riitta; Gutiérrez Aurora García-Camacha (WILEY, 2022)
Background
Individualising the provided care is mandatory in nursing and is essential in clinical practice. Therefore, there is a need to develop accurate instruments to evaluate the quality of care. Moreover, there is no validated instrument to assess nurses’ views of individualised care in Spanish-speaking countries.
Aim
To assess the construct validity and internal consistency of the Spanish version of the Individualised Care Scale-Nurse.
Methods
A cross-sectional study including 108 nursing professionals (40.84 ± 9.51 years old, 86.1% female) was used to validate the Spanish Individualised Care Scale-Nurse version. A forward-back translation method with an expert panel and a cross-sectional study was used for transcultural adaptation and psychometric validation purposes. Psychometric properties of feasibility, reliability and validity were assessed. Construct validity was examined through a confirmatory factor analysis and fit indices of the overall model were computed. Internal consistency was explored through McDonald’s omega and Cronbach’s alpha coefficients among other correlation measures.
Results
The back-translation concluded both Spanish and English Individualised Care Scale-Nurse versions to be equivalent. The original structure of the Individualised Care Scale-Nurse was verified in the Spanish version through the confirmatory factor analysis (factor loadings >0.3; acceptable fit indices: SRMR ≈ 0.08, CFI ≈ 0.9, RMSEA ≈ 0.09 after posteriori modifications). McDonald's omega exceeded 0.7 for both subscales and complete scales revealing an adequate internal consistency.